Successful conversion therapy for unresectable hepatocellular carcinoma is getting closer: A systematic review and meta-analysis - Pei, Yinxuan; Li, Weiwei; Wang, Zixiang; Liu, Jinlong (Frontiers in Oncology, 2022)
Background Conversion therapy provides selected patients with unresectable hepatocellular carcinoma the opportunity to undergo a curative hepatectomy and achieve long-term survival. Although various regimens have been used for conversion therapy, their conversion rate and safety remain uncertain. Therefore, we conducted some meta-analyses to evaluate the efficacy and safety of several conversion regimens in order to elucidate the optimal regimen. Method We performed systematic literature research on PubMed, Embase, and the Web of Science until July 30, 2022. Chemotherapy, transcatheter arterial chemoembolization (TACE), molecular therapy (targeted therapy, immunotherapy, or a combination of both), and combined locoregional-systemic therapy were the conversion regimens we targeted. Results Twenty-four studies were included. The pooled conversion rates for chemotherapy, TACE, molecular therapy, and combined locoregional-systemic therapy were 13% (95% confidence interval [CI], 7%–20%; I² = 82%), 12% (95% CI, 9%–15%; I² = 60%), 10% (95% CI, 3%–20%; I² = 90%), and 25% (95% CI, 13%–38%; I² = 89%), respectively. The pooled objective response rates (ORR) for chemotherapy, TACE, molecular therapy, and combined locoregional-systemic therapy were 19% (95% CI, 12%–28%; I² = 77%), 32% (95% CI, 15%–51%; I² = 88%), 30% (95% CI, 15%–46%; I² = 93%), and 60% (95% CI, 41%–77%; I² = 91%), respectively. The pooled grade ≥3 AEs for chemotherapy, TACE, molecular therapy, and combined locoregional-systemic therapy were 67% (95% CI, 55%–78%; I² = 79%), 34% (95% CI, 8%–66%; I²= 92%), 30% (95% CI, 18%–43%; I² = 84%), and 40% (95% CI, 23%–58%; I² = 89%), respectively. Subgroup analyses showed the conversion rate, ORR and grade ≥3 AE rate for tyrosine kinase inhibitor (TKI) combined with immune checkpoint inhibitor (ICI) and locoregional therapy (LRT) were 33% (95% CI, 17%-52%; I² = 89%), 73% (95% CI, 51%–91%; I² = 90%), 31% (95% CI, 10%-57%; I² = 89%), respectively. Conclusion Combined locoregional-systemic therapy, especially TKI combined with ICI and LRT, may be the most effective conversion therapy regimen, associated with a significant ORR, conversion potential, and an acceptable safety profile.